Prognosis of patients with acute lymphoblastic leukaemia relapsing after allogeneic stem cell transplantation. (18th March 2023) - Ferra Coll, Christelle; Morgades de la Fe, Mireia; Prieto García, Laura; Vaz, Carlos Pinho; Heras Fernando, María Inmaculada; Bailen Almorox, Rebeca; Garcia‐Cadenas, Irene; Calabuig Muñoz, Marisa; Ripa, Teresa Zudaire; Zanabili Al‐Sibai, Joud; Novoa, Sandra; Aguado, Beatriz; et al.
Abstract: The outcomes of patients with acute lymphoblastic leukaemia (ALL) presenting relapse after allogeneic stem cell transplant (allo‐SCT) are poor, with few data available in this setting. Objective and Methods: To evaluate the outcomes of patients with ALL presenting relapsed after allo‐SCT, we performed a retrospective study including 132 from 11 centres in Spain. Results: Therapeutic strategies consisted of palliative treatment ( n  = 22), chemotherapy ( n  = 82), tyrosine kinase inhibitors ( n  = 26), immunotherapy with inotuzumab and/or blinatumumab ( n  = 19), donor lymphocyte infusions ( n  = 29 pts), second allo‐SCT ( n  = 37) and CAR T therapy ( n  = 14). The probability of overall survival (OS) at 1 and 5 years after relapse was 44% (95% confidence interval [CI]: 36%; 52%) and 19% (95% CI: 11%; 27%). In the 37 patients undergoing a second allo‐SCT, the 5‐year estimated OS probability was 40% [22%; 58%]. Younger age, recent allo‐SCT, late relapse, 1st complete remission at 1st allo‐SCT and chronic graft‐versus‐host disease confirmed their positive impact on survival in the multivariable analysis. Conclusion: Despite the poor prognosis of patients with ALL presenting relapse after a first allo‐SCT, some can be satisfactorily rescued and a second allo‐SCT still remains a valid option for selected patients. Moreover, emerging therapies really might improve ALL patients outcome when relapsing after an allo‐SCT.